An overview on FDA-approved natural super disintegrants efficacy in a fast dissolving drug delivery system - Pradhan, Darshan; Chakraborty, Prodipta; Halder, Sudip; Bagchi, Arnab (Creative Pharma Assent, 2021)
FDTs are defined by the United States Food and Drug Administration (FDA) as a solid dosage form containing the therapeutic substance or when applied on the tongue, the active ingredient disintegrates quickly, usually within seconds. The goal of this study is to create a fast-dissolving tablet that uses natural disintegrants. Fast dissolving tablets have grown in popularity in the pharmaceutical industry in recent years. They have a quick disintegration activity that dissolves with saliva without the use of water when placed within the mouth. Furthermore, FDT aims to provide quick medication absorption, reduced toxicity, and higher drug bioavailability, and it is especially popular among geriatric and paediatric patients. Natural disintegrants, which are obtained from natural sources, have a number of advantages, including low cost, nontoxicity, biodegradability, environmental friendliness, and less adverse effects. As a result, it has been established that natural disintegrants are often safer than synthetic disintegrants. Natural disintegrants includes Chitin and chitosan, Guar gum, Gum karaya, Agar and treated agar, Fenugreek seed mucilage, Soy polysaccharide, Gellan gum, Mango peel pectin, Lepidium sativum mucilage, Plantago seed mucilage, Agele marmelos gum, Locust bean gum, Mangifera indica gum, Hibiscus rosa sinensis mucilage, Dehydrated banana powder.